Design and implementation of reconfigurable filter bank structure for low complexity hearing aids using 2-level sound wave decomposition. (May 2018) - A., Amir; T.S., Bindiya; Elias, Elizabeth
Highlights: Reconfigurable digital filter bank structure for hearing aid is proposed. Proposed structure exploits the fractional interpolation and symmetry property of linear phase filters. Using proposed structure, various number of audiograms can be matched with acceptable delay and matching error. The advantages of the proposed structure are low hardware complexity and good audiogram matching with tolerable matching error and acceptable delay. FPGA implementation of the proposed structure is also done. Abstract: This paper proposes a reconfigurable digital filter bank structure, which is suitable for designing hearing aids for most types of hearing losses. The proposed structure exploits the fractional interpolation and symmetry property of linear phase filters. The structure has two stages; the first one is called masking stage and the second one is called multiple passbands generation stage. The second stage i.e., multiple passband generation stage has 2 levels. By adjusting a 7-bit control signal, different sub-bands generated by the two stages can be obtained for audiogram matching. The number of sub-bands can be increased by increasing the number of fractional interpolated filters in level 2 of the multiple passbands generation block. Using the proposed structure, various types of audiograms can be matched with acceptable delay and matching error. The merits of the proposed structure are low hardware complexity and good audiogram matching with tolerable matching error and acceptable delay, when compared to the state of the art techniques for audiogram matching. Moreover, it is a reconfigurable structure. FPGA implementation of the proposed structure is also done to supplement the theoretical claim for low hardware complexity and power.